Evaluation of the cervical vertebral anomalies in patients with cleft lip and palate in Aegean region of Turkey - Ege Dogan; Gulen Ozses Ergican; Servet Dogan (Journal of the Pakistan Medical Association, 2020)
Objective: To identify the cervical vertebral anomalies in patients with cleft lip and palate, and to compare unilateral and bilateral cleft lip and palate. Methods: The retrospective cohort study was conducted in 2018 at Department of Orthodontics, Ege University, Izmir, Turkey, and comprised non-deteriorated lateral cephalometric radiographs of non-syndromic patients which showed the entire cervical spine. The radiographs were divided into two groups, with group A having those of patients with cleft lip and palate exposure, and control group B having those with non-exposure. Within group A, unilateral and bilateral cleft lip and palate cases were compared. Data was analysed using SPSS 22. Results: Of the 220 subjects, 110(50%) were in group A with a mean age of 15±6.3 years, and 110(50%) were in group B with a mean age of 15±2.1 years. Within group A, 56(50.9%) subjects had unilateral and 54(49.1%) had bilateral cleft lip and palate. Cervical vertebral anomalies were found in 71(64.5%) patients and 45(40.9%) controls (p<0.001). Among those with bilateral condition, it was found in 41(75.9%) and in unilateral 56(56.6%) (p<0.05). Occipitalisation was 21(38.9%) in bilateral and 4(7.1%) in unilateral cases (p<0.001). Fusion was higher in bilateral patients 16(63%) compared to 23(41.1%) unilateral (p<0.05). Posterior arch deficiencies were found in 30(27.3%) patients in group A and 18(16.4%) controls in group B (p<0.05). Fusion was seen in 57(51.8%) group A patients and 33(30%) group B controls (p<0.001). Conclusion: Cervical vertebral anomalies were mostly found in patients with cleft lip and palate. Continuous....